KEHILANGAN TENAGA AKIBAT PERUBAHAN KECEPATAN ALIRAN, KEKASARAN DAN LUAS PENAMPANG PIPA PADA PENGALIRAN DALAM PIPA - Pujianiki, Nyoman; Susanto, Bambang (Jurnal Ilmiah Teknik Sipil; Vol. 9, No. 2 Juli 2005)
Flowing water by pipe is mostly used to distribute the water from its sources to taps for various needs. On the way of distribution, it meets some obstacles, i.e.: velocity, surface and roughness changing. Thus, the research has been done in order to know the influences of all the changes of the head loss on the 1 meter pipe. This research used Fluid Friction Apparatus complete with hydraulic bench and manometer. Variation of flowing on pipe has done for 50 times, using each 6 mm and 10 mm and four 17.5 mm pipe with different roughness which consist of different sands diameter. From that research we found out that there’s a similarity in velocity and roughness with head loss showing polynomial order 2 ( hf = a + bu + cu2 and hf = a + bk + ck2 ) where much velocity and roughness causing higher head loss. While pipe surface inverse proportional to head loss that shows exponential relationship (hf = a e –bA) where more surface causing less head loss.
Keywords: velocity, roughness, pipe surface, head loss, pipe